Rodzina i jej znaczenie w uczeniu się roli ojca przez współczesnych mężczyzn. Biograficzne konteksty - Ratajczak, Łukasz P. (Studia Edukacyjne, 2020)
The article takes into consideration the importance of the family in the context of men preparing to assume the role of a modern father. Equally, it emphasizes the significance of the learning process, a result of a transmission of experiences. It claims that the family of origin and the family of one’s own make up the educational potential supporting young adults in building their concept of parenthood.